Breast size and risk of type 2 diabetes mellitus - Ray, Joel G. (Canadian Medical Association, 2008)
BACKGROUND: Elevated waist circumference and body mass index (BMI), both traditional measures of obesity, are accepted risk factors for type 2 diabetes mellitus. Girls who are obese experience earlier onset of puberty and possibly greater breast development. We sought to evaluate whether a woman's breast size in late adolescence is associated with an increased risk of type 2 diabetes mellitus in adulthood. METHODS: In conjunction with the ongoing Nurses' Health Study II, which began to study risk factors for breast cancer among women in 1989, we conducted a prospective cohort study involving 92 106 of the participants. We assessed the risk of type 2 diabetes mellitus in relation to self-reported bra cup sizes, categorized as ≤ A, B, C and ≥ D cups, among participants at age 20. RESULTS: The mean age of participants at baseline was 38.1 years. A total of 1844 new cases of type 2 diabetes mellitus arose at a mean age of 44.9 years during 886 443 person-years of follow-up. Relative to bra cup size ≤ A, the respective age-adjusted hazard ratios (and 95% confidence intervals [CIs]) were 2.30 (1.99–2.66) for B cup, 4.32 (3.71–5.04) for C cup and 4.99 (4.12–6.05) for ≥ D cup. Upon further adjustments for age at menarche, parity, physical activity, smoking status, diet, multivitamin use, family history of diabetes mellitus, BMI at age 18 and current BMI, the corresponding hazard ratios (and 95% CIs) were 1.37 (1.18–1.59) for B cup, 1.80 (1.53- 2.11) for C cup and 1.64 (1.34–2.01) for ≥ D cup. The addition of waist circumference to this model minimally changed the hazard ratios (and 95% CIs): 1.32 (1.14–1.53) for B cup, 1.71 (1.46–2.01) for C cup and 1.58 (1.29–1.94) for ≥ D cup. INTERPRETATION: A large bra cup size at age 20 may be a predictor of type 2 diabetes mellitus in middle-aged women. Whether this relation is independent of traditional indicators of obesity remains to be determined.